2018
DOI: 10.1038/s41598-018-21291-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional ultrastructural analysis of the interface between an implanted demineralised dentin matrix and the surrounding newly formed bone

Abstract: Previous investigators have reported that transplanted demineralised dentin matrix (DDM) influences bone formation in vivo. However, the specific mechanism of how dentinal tubules contribute to bone formation has not been determined with regard to DDM transplantation therapy. In this study, we ultrastructurally investigated how DDM contacted the surrounding newly formed bone using a scanning electron microscopy (SEM) three-dimensional reconstruction method that is based on focused ion beam slicing and SEM (FIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…From Tanoue et al Reproduced under the terms of the Creative Commons Attribution License (CC BY 4.0). 216 c Sample preparation for transmission electron microscopy using the in situ lift-out technique, starting with deposition of a 30 µm long, 2 µm wide, and 1 µm-thick protective layer, followed by sequential milling, lift-out, and thinning to electron transparency. From Grandfield et al Adapted with permission from John Wiley and Sons.…”
Section: Fib-sem For 3d Imaging and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…From Tanoue et al Reproduced under the terms of the Creative Commons Attribution License (CC BY 4.0). 216 c Sample preparation for transmission electron microscopy using the in situ lift-out technique, starting with deposition of a 30 µm long, 2 µm wide, and 1 µm-thick protective layer, followed by sequential milling, lift-out, and thinning to electron transparency. From Grandfield et al Adapted with permission from John Wiley and Sons.…”
Section: Fib-sem For 3d Imaging and Sample Preparationmentioning
confidence: 99%
“…215 Likewise, the attachment of osteocytes via cell processes to demineralised dentin matrix particles implanted in the rat calvarium has also been studied using FIB tomography. 216…”
Section: Fib-sem For 3d Imaging and Sample Preparationmentioning
confidence: 99%
“…Urist suggested that, if the dentin matrix undergoes biodegradation or resorption through a remodeling process after grafting, disintegration of covalent bonding occurs and releases osteoinductive proteins, which play a key role in stimulating stem cells in the surrounding tissues and causing phenotypic changes to produce osteoblasts2. This mechanism has been determined by several in vitro and in vivo studies1617183536.…”
Section: Incorporation Of Rhbmp-2 With Ddm (Ddm/rhbmp-2)mentioning
confidence: 99%
“…(Fig. 3; green line) This process is accelerated via both dentinal tubule and interfibrillar space pores and is induced by collagenolytic degradation or osteoclastic resorption, which might start at the beginning of implantation but before the actual release of proteins11736.…”
Section: The Postulated Release Profile Of Rhbmp-2 From the Ddm (mentioning
confidence: 99%
“…The FIB can be extremely narrow in diameter (1–1,000 nm) and sputters a very thin layer from the tissue block surface. It can mill even hard tissues, such as tooth or bone (Tanoue et al, 2018 ). These features are valuable and unique to the FIB-SEM; the other microscopies cannot achieve such a thin layer cutting nor hard tissue sectioning (Briggman and Bock, 2012 ; Kubota, 2015 ).…”
Section: Automated Serial Block Face Image Acquisition Scanning Electmentioning
confidence: 99%